Mapping the Future of the Economy: Synergy of EBT Investment, Human Resource Development, and Fintech Innovation - Cecilia, Putri Engellina; Zahro, Amellia; Budianto, Eka Wahyu Hestya (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study analyzes the influence of renewable energy investment, Human Development Index (HDI), and fintech lending on Indonesia's economic growth in the context of a green economy. Using quantitative methods with multiple linear regression, this study processes time series data from 2018 to 2022 through Eviews. The results show that renewable energy investment and HDI have a significant positive effect on economic growth, while fintech lending has a significant negative effect. Renewable energy investment encourages employment and innovation, while increasing HDI increases productivity. Fintech lending causes problems such as high default rates, especially in lower-middle-class communities. The model explains 93.8496% of the variation in economic growth. These findings emphasize the importance of holistic development policies and appropriate regulations for financial innovation in supporting Indonesia's green economic growth